SEG Technical Program Expanded Abstracts 2017 2017
DOI: 10.1190/segam2017-17663038.1
|View full text |Cite
|
Sign up to set email alerts
|

Wave-equation dispersion inversion of surface waves recorded on irregular topography

Abstract: CitationLi J, Schuster GT, Lin F-C, Alam A (2017) SUMMARYSignificant topographic variations will strongly influence the amplitudes and phases of propagating surface waves. Such effects should be taken into account, otherwise the S-velocity model inverted from the Rayleigh dispersion curves will contain significant inaccuracies. We now show that the recently developed wave-equation dispersion inversion (WD) method naturally takes into account the effects of topography to give accurate S-velocity tomograms. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
0
15
2
Order By: Relevance
“…We use the multioffset WDG strategy to invert for the P-velocity model using the conjugate-gradient method (J. Li, Lin, et al, 2017). Figure 7f shows the WDG tomogram after 25 iterations, and the predicted dispersion curves shown in Figure 8a (black solid lines) resemble the observed values (black dashed lines).…”
Section: Two-layer Model With An Irregular Interfacementioning
confidence: 92%
See 1 more Smart Citation
“…We use the multioffset WDG strategy to invert for the P-velocity model using the conjugate-gradient method (J. Li, Lin, et al, 2017). Figure 7f shows the WDG tomogram after 25 iterations, and the predicted dispersion curves shown in Figure 8a (black solid lines) resemble the observed values (black dashed lines).…”
Section: Two-layer Model With An Irregular Interfacementioning
confidence: 92%
“…Inverting the Love waves gives a low-S-velocity tomogram in the middle of site 2 (J. Li, Lin, et al, 2017).…”
Section: Qademah Field Datamentioning
confidence: 99%
“…At local (exploration) scales, Nuber et al (2016) showed that neglecting topography with an amplitude fluctuation greater than half the minimum seismic wavelength leads to appreciable inversion artifacts. Similarly, Li et al (2017) demonstrated the importance of including topography when inverting for S-wave velocity from Rayleigh wave dispersion curves. Although these studies were done for smaller scales and shorter wavelengths where the effect of topography is clearly larger than in our case, we will find that topography may need to be included for regional wave propagation at intermediate periods.…”
Section: Modelling Wave Propagation In Ice-covered Regionsmentioning
confidence: 93%
“…; Li et al . ). Such information is important for earthquake research, seismology and near‐surface engineering studies (Xia, Miller and Park ; Lin, Moschetti and Ritzwoller ; Li and Hanafy ; Liu et al .…”
Section: Introductionmentioning
confidence: 97%
“…To mitigate this problem, Li et al . () and Li, Feng and Schuster () presented the theory for inverting dispersion curves associated with lateral and vertical variations in the velocity model. The misfit function is the sum of the squared wavenumber differences between the predicted and observed dispersion curves, and the inverted result is a moderate‐to‐high‐resolution estimate of the near‐surface S‐velocity model.…”
Section: Introductionmentioning
confidence: 99%